FUNDIAL REGULARIZATION IN PERMANENT PRESERVATION ARE: CASE STUDY IN ENTRE-IJUÍS CITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article reports the disordered growth of cities that reached the permanent preservation area, case study in Entre-Ijuís, State of Rio Grande do Sul. In this work, the ways to remedy these area for Land Regularization will be addressed, without causing further damage to the environment. The objective is to present Reurb's fundamentals in a permanent preservation area, Reurb-S and the guarantee of decent and adequate housing for the occupants. The method covered will be bibliographic and documentary research.